2012
DOI: 10.1152/ajplung.00046.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke and its component acrolein augment IL-8/CXCL8 mRNA stability via p38 MAPK/MK2 signaling in human pulmonary cells

Abstract: Interleukin-8 (IL-8/CXCL8) is an important neutrophil chemoattractant known to be elevated in the airways of cigarette smokers and in patients with chronic obstructive pulmonary disease (COPD). We examined the acute effect of aqueous cigarette smoke extract (CSE) on IL-8 expression in primary human pulmonary cells, in particular in normal human bronchial smooth muscle cells (HBSMCs). IL-8 mRNA levels increased upon CSE exposure in a concentration- and time-dependent manner, and such an effect was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 43 publications
7
57
1
Order By: Relevance
“…These drugs also reduce CXCL8 mRNA stabilization in CSE-exposed alveolar macrophages [15]. We would therefore expect p38 MAPK inhibitors to also reduce CXCL8 production from COPD alveolar macrophages exposed to CSE and then LPS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These drugs also reduce CXCL8 mRNA stabilization in CSE-exposed alveolar macrophages [15]. We would therefore expect p38 MAPK inhibitors to also reduce CXCL8 production from COPD alveolar macrophages exposed to CSE and then LPS.…”
Section: Discussionmentioning
confidence: 97%
“…As described previously [15], cell pellets were lysed in Trizol (Invitrogen, Paisley, UK) for RNA extraction and PCR analysis for CXCL8, TNF-α, TLR-2, TLR-4 and TLR-5. Total RNA was purified from cell lysates using the RNeasy Mini Kit (Qiagen, Crawley, UK), according to the manufacturer's instructions.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr) Analysismentioning
confidence: 99%
“…MK2 appears to play a role in prolonging NF-kB activation in Th2 cells and therefore amplifies allergic inflammation (Gorska et al, 2007). MK2 is also important in mediating the increased release of CXCL8 in response to cigarette smoke in human airway smooth muscle cells (Moretto et al, 2012). However, ATPcompetitive MK2 inhibitors have poor selectivity and low solubility (Schlapbach and Huppertz, 2009).…”
Section: G Mapkapk2 Inhibitionmentioning
confidence: 99%
“…Research has concluded that IL-6 induces lung inflammatory processes by way of Stat3 and promotes emphysema through the upregulation of alveolar cell apoptosis independent of Stat3 in emphysema and COPD, thereby suggesting that IL-6 trans-signaling and Stat3 hyperactivation may provide potential disease biomarkers and therapeutic targets (106). Additionally, a recent study has provided evidence for the initiation of the p38 MAPK and MAPKactivated kinase-2 (MK2) phosphorylation pathways by the CS-induced translation of IL-8 mRNA in bronchial smooth muscle cells (BSMC) (85). This being said, because IL-8 is a chemoattractant, it is suggested that CS may directly recruit neutrophils and propagate inflammation in BSMC by this mechanism.…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%